Impossible Properties: Language And Legitimacy In Ong Keng Sen's Lear - Edwards, James (Penerbit Universiti Sains Malaysia (USM Press), 2014)
This paper explores a landmark production in the history of Asian intercultural theatre, Singaporean director Ong Keng Sen and Japanese playwright Kishida Rio's Lear (1997/1999). A lavish production underwritten by the Japan Foundation Asia Center, Lear helped establish Ong's "fiercely intercultural" aesthetic as an internationally recognisable brand (Peterson 2003: 81). It also drew critique as a symbolic apologia for neoliberal globalisation. The critical literature on Lear has yielded trenchant insights into the global political significance of intercultural performance. At the same time, however, it has tended to overshadow questions of the work's aesthetic specificity and local significance. This paper seeks to recuperate Lear's local meanings both as a text and as a uniquely Singaporean political allegory. In the paper's first section, I will outline the play and its critique as late capitalist spectacle. In the following section, I will bracket this critique and return to the texts at hand. Finally, I will move back outward by tracing a Brechtian tension between Kishida's text, Ong's realisation, and the Singaporean state's "choreography" of racial, cultural and linguistic difference.